Sistem Monitoring Kualitas Air Menggunakan Sensor Turbidity Metode Nephelometri Berbasis Raspberry PI 3 - Goib Wiranto; Tri Rahajoeningroem; Al Fatin Fernanda (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2020)
n this research it has designed a turbidity sensor system to determine the parameters of turbidity in water that can be consumed, using the nephelometry method. Nephelometry is a method in utilizing the nature of light scattering, light sources emitted into water media containing particles that will be scattered and detected by light detectors positioned at 90 Â° angle. In this work the light source was used a super bright red LED and a TSL 250r photodiode light detector with a wavelength of 630nm. This paper will also explain process of making sensor and the turbidimeter system on the basis of Raspberry Pi 3. The results of the turbidimter sensor characterization obtained with the least square equation are y = 232.51x-61.29, the formula is can be used to change the ADC value to NTU (Nephelometer Turbidity Unit). The turbidity sensor has an accuracy of a minimum value is 2 NTU and a maximum value is 200 NTU with an error under 5%.